Protection of short-time enamel erosion by different tetrafluoride compounds - Wiegand, Annette; Laabs, Koija Alexander; Gressmann, Grit; Roos, Malgorzata; Magalhaes, Ana Carolina [UNESP]; Attin, Thomas (Pergamon-Elsevier B.V. Ltd, 2008)
objective: This in vitro study aimed to analyse the protective effect of differently concentrated titanium (TiF4), zirconium (ZrF4) and hafnium (HfF4) tetrafluoride on enamel erosion. Methods: Polished enamel surfaces of 36 bovine crowns were covered with tape leaving 4 enamel windows each 3 mm in diameter exposed. The crowns were randomly assigned to six groups (each n = 6) and pretreated with 4% TiF4, 10% TiF4, 4% ZrF4, 10% ZrF4, 4% HfF4 or 10% HfF4 for 4 min (first window), 10 min (second window) or 15 min (third window). The fourth window of each crown was not pretreated and served as control. Erosion was performed stepwise with 1% HCl (pH 2) in five consecutive intervals of each 15 s (total 75 s). Enamel dissolution was quantified by colorimetric determination of phosphate release into the acid. For each tooth, cumulative phosphate loss of enamel pretreated with one of the tetrafluoride compounds was calculated as percentage of the respective control and statistically analysed using two-way ANOVA.Results: Enamel erosion was significantly reduced by TiF4, ZrF4 and HfF4 application. Cumulative phosphate loss (mean % of control, 75 s erosion) after 4-15 min application was significantly lower for 4% ZrF4 (7-11%), 10% ZrF4 (2-6%), 4% HfF4 (11-9%) and 10% HfF4 (12-16%) compared to 4% TiF4 (42-27%) and 10% TiF4 (54-33%). Only for 4% and 10% TiF4, phosphate loss decreased with increasing duration of application, but also increased with increasing acid intervals.Conclusion: TiF4, ZrF4 and HfF4 might protect enamel against short-time erosion, but protection was more enhanced by ZrF4 and HfF4 compared to TiF4 application overtime. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: enamel; erosion; fluoride